Systemic disease activity measured with ESSDAI varies largely over 5 years in a prospective, longitudinal cohort of patients with Sjögren’s disease - Suzanne Arends; Arjan Vissink; Hendrika Bootsma; Liseth de Wolff; Gwenny Verstappen; Alja Stel; Greetje van Zuiden; Jolien van Nimwegen; Frans Kroese (RMD Open)
Objectives The objectives are to evaluate variation in systemic disease activity (European Alliance of Associations For Rheumatology (EULAR) Sjögren’s Syndrome Disease Activity Index (ESSDAI)) over time at group and individual patient level and to assess associations of ESSDAI low disease activity (LDA) with other outcome measures in a standard-of-care cohort of patients with Sjögren’s disease (SjD).Methods Patients with SjD participating in a prospective longitudinal study (REgistry of Sjögren Syndrome LongiTudinal cohort) fulfilling the 2016 American College of Rheumatology/EULAR classification criteria with ≥2 years of follow-up were included. ESSDAI was assessed at least yearly, up to 5 years. Patient-reported, objective glandular and laboratory outcomes were compared between patients with ESSDAI LDA (score<5) for <75% vs ≥75% of time.Results Of 265 included patients with SjD, 236 (89%) were women, median disease duration was 6 years (IQR 2–10) and 114 (43%) received immunosuppressive treatment at some point during follow-up. At group level, median ESSDAI decreased slightly, from 4 (IQR 2–7) at baseline to 3 (IQR 2–5) at year 5, with a concomitant decrease in variation, indicating regression to the mean. At the individual patient level, ESSDAI varied in the majority of patients: 50/102 (49%) untreated patients with ESSDAI<5 at baseline changed to ESSDAI≥5 at least once during follow-up. Of the untreated patients with ESSDAI≥5 at baseline, 41/45 (91%) changed to ESSDAI<5. Patients with ESSDAI LDA for ≥75% of time showed better outcomes on saliva production.Conclusions In this cohort of patients with SjD, overall ESSDAI slightly decreased during 5 years of follow-up, whereas at individual patient level, large variation was seen over time for the majority of patients. Longer time in ESSDAI LDA was associated with better salivary gland outcomes.